Alterações do ciclo sono-vigília moduladas por Dopamina e suas consequências Mnemônicas - Franca, Arthur Sergio Cavalcanti de (2012)
Neuroscience is on a rise of discoveries. Its wide interdisciplinary approach facilitates a more complex understanding of the brain, covering various areas in depth. However, many phenomena that fascinate human kind are far from being fully elucidated, such as the formation of memories and sleep. In this study we investigated the role of the dopaminergic system in the process of memory consolidation and modulation of the phases of sleep-wake cycle. We used two groups of animals: wildtype mice and hiperdopaminergic mice, heterozygous for the gene encoding the dopamine transporter protein. We observed in wild-type mice that the partial blockade of the D2 dopamine receptor by the drug haloperidol caused deficits in memory consolidation for object recognition, as well as a significant reduction in the duration of rapid eye movement sleep (REM). We also found a mnemonic deficit without pharmacological intervention in hiperdopaminergic animals; this deficit was reversed with haloperidol. The results suggest that dopamine plays a key role in memory consolidation for object recognition. The data also support a functional relationship between the dopaminergic system and the modulation of REM sleep